(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
B.F Skinner has written one of the most extensive autobiographies in the history of science. However, little attention was paid to the peculiarities and intellectual value of this research source. To deal with this historiographical gap, the aim of this article is to present Skinner’s autobiographical narrative as a document with unexplored theoretical possibilities in the historiography of his science. The argument defended is that Skinner’s autobiography has a significant epistemological and historiographical value by exposing an unprecedented interpretation of scientific behavior in the body of his work. Finally, I assess Skinner’s autobiography as a source capable of bringing his philosophy and science of behavior in line with relevant contemporary debates in the human and social sciences.